ChemInform Abstract: C(sp2)—C(sp2) Cross Coupling Reaction Catalyzed by a Water‐Stable Palladium Complex Supported onto Nanomagnetite Particles. Issue 23 (June 2015) - Azadbakht, Tahereh; Zolfigol, Mohammad Ali; Azadbakht, Reza; Khakyzadeh, Vahid; Perrin, David M.
Abstract Diaryl compounds (III) are efficiently, simply, and cost‐effectively synthesized by Suzuki reaction using a palladium complex supported onto magnetite nanoparticles as easily recyclable and stable catalyst.